'This place is not normal': mobile workers and HIV/AIDS. (1st January 2014) - Bulman, Donna; Mathews, Maria; Dykeman, Margaret; Gustafson, Diana L.; Keough, Fran
This qualitative research study explores lifestyle changes associated with mobile work that may put one at risk for acquiring HIV/AIDS or other STIs. Data collection occurred between 2008 and 2011. Sixteen men and women from Atlantic Canada participated. All participants had worked in the oil sands at Fort McMurray and had travelled back to Atlantic Canada at least once in the year prior to data collection. Participants discussed lifestyle factors related to mobility and 'place' that might put them at risk for acquiring HIV/AIDS or other STIs. A thematic analysis was completed. Social disruption, the environment, workplace safety policies, and limited health services contributed to risky behaviours that could put participants at risk for acquiring HIV/AIDS or other STIs. Additional research, including ethnographic studies, is required prior to making recommendations to influence health promotion, harm reduction and occupational health and safety policies.